“In the interest of the Indians”: The Department of Indian Affairs, Charles Cooke and the recruitment of Native Men in Southern Ontario for the Canadian Expeditionary Force, 1916 - McGowan, Katharine (Ontario History, 2010)
When the Canadian Expeditionary Force (CEF) began actively enlisting Native men for overseas service in December 1915, the Department of Indian Affairs (DIA) saw an opportunity to further their goal of assimilating Native peoples through active duty. To maximize the number of Native soldiers, the DIA lent Iroquois clerk and translator Charles Cooke to the CEF to help recruit on reserves in Southern Ontario in the winter and spring 1916. During the northern half of Cooke’s tour from Rama to Manitoulin Island, many of the communities he visited took advantage of his connection with the DIA, using the current need for soldiers as a bargaining chip in pre-war disputes with the government. While they used Cooke to further their local concerns, he judged the Native men’s potential abilities as soldiers, as well as the strength of their communities, according to the tenets of the DIA’s goal of assimilating Native peoples.